Assessment of Cardiac Involvement in Fabry Disease (FD) with Native T1 Mapping - Roller, Fritz Christian; Fuest, Sven; Meyer, Marco; Harth, Sebastian; Gündüz, Dursun; Bauer, Pascal; Schneider, Christian; Rolfs, Arndt; Krombach, Gabriele Anja; Tanislav, Christian (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2019)
Purpose Fabry disease (FD) is an X-linked multi-organ disorder of lysosomal metabolism with cardiac disease being the leading cause of death. Identifying early FD-specific pathologies is important in the context of maximum therapeutic benefit in these stages. Therefore, the aim of this study was to investigate the value of quantitative cardiac T1 mapping as a potential disease-specific surrogate.Methods 16 consecutive FD patients (9 female, 7 male; median age: 54 years, IQR 17) and 16 control patients (9 female, 7 male; median age: 52 years, IQR 20) were investigated at 1.5 Tesla. Native T1 mapping was performed using a modified look locker inversion recovery sequence (MOLLI) and native T1 times were measured within the septal myocardium at the midventricular short-axis section. Also functional parameters, left ventricular morphology, presence of late-gadolinium enhancement, cTnI- and Lyso-Gb3-Levels were evaluated.Results The median native septal T1 time for FD was 889.0 ms and 950.6 ms for controls (p < 0.003). LGE and positive cTnI values (0.26 ± 0.21) were present in 5 FD patients (31.25 %), and left ventricular hypertrophy (LVH) was present in 4 FD patients (25.00 %). The 4 cTnI and 8 Lyso-Gb3 positive FD patients had significantly lower native T1 values (p < 0.05, respectively p < 0.01). Assuming a T1 cut-off value of 900 ms for the identification of increased cardiac lipid deposit, 9 patients with FD (56.25 %) had pathologic values (4 patients cTnI and 8 patients Lyso-Gb3 positive). Moreover, native septal T1 showed a good negative correlation to Lyso-Gb3 (r = – 0.582; p = 0.018).Conclusion A pathologic cardiac native T1 time obviously reflects cardiac involvement in the scope of FD at tissue level. In the future native T1 mapping as an imaging biomarker might allow identification of early stages of cardiac involvement in FD before morphological changes are obvious.Key Points: Citation Format
Keywords: cardiac; technical aspects; MR imaging